2021
DOI: 10.4078/jrd.2021.28.1.31
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Tinnitus on Fibromyalgia

Abstract: Objective Fibromyalgia (FM) is a disorder characterized by chronic diffuse pain and enhanced pain response to stimuli and is caused by central sensitization Tinnitus also is related to central sensitization So we investigated the impact of tinnitus on FM Methods We included 22 FM patients with tinnitus and 25 FM patients without tinnitus We assessed a range of symptoms using the Widespread Pain Index; Symptom Severity Score scale; Visual Analogue Scale of pain; and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Similarly, Chung et al [21] demonstrated that 46.8% and 87.2% of the 47 FM patients had tinnitus and headache, respectively, suggesting a high incidence of these symptoms in FMS. They proposed that tinnitus is an important aspect of centrally related symptoms in FM, implying that the degree of tinnitus corresponds directly to the severity of FM and should be investigated in all FM patients.…”
Section: Discussionmentioning
confidence: 83%
“…Similarly, Chung et al [21] demonstrated that 46.8% and 87.2% of the 47 FM patients had tinnitus and headache, respectively, suggesting a high incidence of these symptoms in FMS. They proposed that tinnitus is an important aspect of centrally related symptoms in FM, implying that the degree of tinnitus corresponds directly to the severity of FM and should be investigated in all FM patients.…”
Section: Discussionmentioning
confidence: 83%
“…Preliminary data suggest a higher handicap relating to the presence of dizziness in patients with fibromyalgia compared to controls [49]. Furthermore, a recent, small-scale cross sectional study of the impact of tinnitus in fibromyalgia provides preliminary support for the link with central sensation as the severity of tinnitus was associated with severity of overall symptoms of fibromyalgia, and poorer quality of life [15]. Self-reported hearing loss, amongst other sensory symptoms, has also been previously shown to be more prevalent amongst patients with fibromyalgia compared to those with other rheumatic conditions, adjusting for age and sex [67].…”
Section: Discussionmentioning
confidence: 99%
“…Туа біткен даму ақаулар жалғыз немесе қосарланған болуы мүмкін және олар аса маңызды немесе аз клиникалық мәнге ие. Жаңа туылған нәрестелердің шамамен 14% -ында жалғыз шағын ақаулар байқалатындығы дәлелденген [5]. Италияндық ғалым Р.Бертоллинидің зерттеуінде «барлық жүктіліктің шамамен 40% жүктіліктің алғашқы екі аптасында түсік тастаумен аяқталатыны анықталды, тағы 10% жүктілік жүктіліктің 70-ші күніне дейін өздігінен түсік түсірумен аяқталады.…”
unclassified